2021
DOI: 10.3389/fpls.2021.644528
|View full text |Cite
|
Sign up to set email alerts
|

Cold Hardiness Dynamics and Spring Phenology: Climate-Driven Changes and New Molecular Insights Into Grapevine Adaptive Potential

Abstract: Climate change has become a topic of increasing significance in viticulture, severely challenged by this issue. Average global temperatures are increasing, but frost events, with a large variability depending on geographical locations, have been predicted to be a potential risk for grapevine cultivation. Grape cold hardiness encompasses both midwinter and spring frost hardiness, whereas the avoidance of spring frost damage due to late budbreak is crucial in cold resilience. Cold hardiness kinetics and budbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 137 publications
(190 reference statements)
0
10
0
Order By: Relevance
“…Kovaleski et al (2018) suggested that the growth of Vitis riparia was earlier and the deacclimation rates of V. riparia and Vitis amurensis were faster at low above‐freezing temperatures compared with those of V. vinifera varieties. The earlier bud growth of hardy species might be explained by the evolutionary necessity for rapid development during short growing seasons (Ferguson et al, 2014; De Rosa et al, 2021). ‘Yamasachi’ was developed by crossing ‘Seibel 13053’ as the seed parent with a local wild mountain grape (probably V. amurensis ) as the pollen parent.…”
Section: Discussionmentioning
confidence: 99%
“…Kovaleski et al (2018) suggested that the growth of Vitis riparia was earlier and the deacclimation rates of V. riparia and Vitis amurensis were faster at low above‐freezing temperatures compared with those of V. vinifera varieties. The earlier bud growth of hardy species might be explained by the evolutionary necessity for rapid development during short growing seasons (Ferguson et al, 2014; De Rosa et al, 2021). ‘Yamasachi’ was developed by crossing ‘Seibel 13053’ as the seed parent with a local wild mountain grape (probably V. amurensis ) as the pollen parent.…”
Section: Discussionmentioning
confidence: 99%
“…Although the leading threat posed to the survival of grapevine in winter is low temperatures that exceed the lethal threshold, an emerging issue is the prolonged period of warmth in fall because of climate change 45,58 . As the first potential consequence, cold acclimation, which is progressively induced by low above and below freezing temperatures, may be compromised.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, for putative evolutionary reasons, deacclimation was observed to proceed much faster in wild species such as Vitis riparia and Vitis amurensis, routinely used by breeders to introduce resistant phenotypes in V. vinifera. Therefore, a better understanding of dormancy physiology and regulation also for these species is desirable [40].…”
Section: Introductionmentioning
confidence: 99%